Pulmonary mucoepidermoid carcinoma in children: two case reports and a review of the literature - Huang, Yuan; Fu, Yong; Sun, Jing; Xu, Bin; Wu, Lei; Tang, Lan-fang (Frontiers in Pediatrics, 2023)
Pulmonary mucoepidermoid carcinoma (PMEC) is a rare tumor, particularly in children, and its clinical manifestations vary. When the tumor is small, it may be asymptomatic; however, with larger tumors, patients may present with symptoms such as recurring pneumonia, atelectasis, persistent cough, chest pain, and even hemoptysis. PMEC appears as an exophytic intrabronchial mass. This study aims to report on the clinical manifestations, imaging findings, treatment approaches, and prognosis of two children diagnosed with PMEC at our hospital between January 2018 and December 2022. The age of onset for both children was nine years, and the masses were located in the right upper lobe bronchi. Following surgical treatment, both patients showed a good prognosis. In addition, we conducted a comprehensive review of the relevant literature to enhance the overall understanding of PMEC.